Cultural heritage, incentives system and the sustainable community:lessons from Ogimachi Village, Japan - Indera Syahrul Mat Radzuan; Fukami, Naoko; Yahaya Ahmad (Faculty of Social Sciences and Humanities, UKM,Bangi, 2014)
Historic villages normally connote settlements that reflect the combination of natural, cultural and social characteristics of the urban and sub-urban fabric of pre-modern era which existence is not neglected by modernization. In highly developed and modernized Japan, there are numerous public incentives provided by the authorities to conserve historic buildings, villages and areas but the most challenging part of the task is to realize the principles and goals of sustainable communities. This refers to making the decision making process inclusive and equitable, recognizing the diversity and differences of the community participations that cut across gender, political, cultural and social lines. This study seeks to understand how the concept of public inclusiveness has been implemented by the local authorities. Field interviews involved officials and residents of the historic Ogimachi Village at Shirakawa-go in Gifu Prefecture. Results revealed that relatively little consideration had been given to regenerate the intangible heritage aspects of this historic village such as drama, music and festivals, language and works of art, manners and customs, folk performing arts, and religious faith. The basic lesson that may be drawn from this Japanese experience of heritage settlements is that any effort to preserve cultural heritage should be aimed not merely at conserving its architectural and natural forms, but more fundamentally, at safeguarding the intangible components of the heritage. Hence, future research should further our understanding of the historic village as a living system which is capable of evolving without losing its identity.